Monophyletic origin and evolution of the largest crucifer genomes - Mandáková, Terezie; German, Dmitry (Plant physiology, 2017)
Clade E, or the Hesperis clade, is one of the major Brassicaceae (Crucifereae) clades, comprising some 48 genera and 351 species classified into seven tribes and is distributed predominantly across arid and montane regions of Asia. Several taxa have socioeconomic significance, being important ornamental but also weedy and invasive species. From the comparative genomic perspective, the clade is noteworthy as it harbors species with the largest crucifer genomes but low numbers of chromosomes (n = 5-7). By applying comparative cytogenetic analysis and whole-chloroplast phylogenetics, we constructed, to our knowledge, the first partial and complete cytogenetic maps for selected representatives of clade E tribes and investigated their relationships in a family-wide context. The Hesperis clade is a well-supported monophyletic lineage comprising seven tribes: Anchonieae, Buniadeae, Chorisporeae, Dontostemoneae, Euclidieae, Hesperideae, and Shehbazieae. The clade diverged from other Brassicaceae crown-group clades during the Oligocene, followed by subsequent Miocene tribal diversifications in central/southwestern Asia. The inferred ancestral karyotype of clade E (CEK; n = 7) originated from an older n = 8 genome, which also was the purported progenitor of tribe Arabideae (KAA genome). In most taxa of clade E, the seven linkage groups of CEK either remained conserved (Chorisporeae) or were reshuffled by chromosomal translocations (Euclidieae). In 50% of Anchonieae and Hesperideae species, the CEK genome has undergone descending dysploidy toward n = 6 (−5). These genomic data elucidate early genome evolution in Brassicaceae and pave the way for future whole-genome sequencing and assembly efforts in this as yet genomically neglected group of crucifer plants.
Gesehen am 12.09.2018